DYNAMIC CAPABILITY THEORY: PERSPEKTIF AKUNTANSI - Evayani, Evayani; Mutia, Evi; Saleh, Muhammad; Rahmawati, Syarifah (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
Dynamic capabilities are described as a company's ability to change, and given the changing environment. The dynamic capabilities perspective is in its efforts to explain competitive advantage in a dynamic environment. Currently, dynamic capabilities have been implemented in various aspects, including, marketing, production, resources, and also accounting. The purpose of this study is to provide an overview of the application of Dynamic Capability Theory, viewed from an accounting perspective. This research method is descriptive analysis. The analysis, found that dynamic capability theory, through an accounting perspective, is related to the fields of sharia accounting, government accounting, accounting information systems, financial accounting and corporate governance. The analysis carried out descriptively is a limitation of this study. Therefore, it is recommended that in the future, it can be done by interviewing stakeholders.